Hannani Clinic Appointment System with D-OTP (HCAS) - NAGALINGAM, DHESHINI; Khairul Amin Mohamad Sukri, (Applied Information Technology And Computer Science, 2025)
The Hannani Clinic Appointment System with D-OTP (HCAS) is a comprehensive web-based platform designed to enhance appointment scheduling for patients at Clinic Dr Hannani, while ensuring robust data security. Utilizing an object-oriented approach, the system employs HTML, CSS, and JavaScript for development and styling, and MySQL with SQL queries for database management, guided by an Entity-Relationship Diagram (ERD). The primary objectives of this application are to design an email-based One Time Password (D-OTP) integration, develop the HCAS as a web-based platform, and rigorously test its functionality. This chapter outlines the implementation and testing of a security model within HCAS, incorporating features such as session kill, encryption, password strength validation, username and email validation, account lockout, one-time passcode (OTP), and reCaptcha. The methodology involved coding, integrating these security features, and rigorously testing each module to ensure functionality and effectiveness. Testing results confirm that HCAS operates seamlessly, providing a user-friendly interface with advanced security measures, ensuring that all components function as intended and offer robust protection for user data. In conclusion, HCAS successfully integrates efficient scheduling capabilities with comprehensive security features, offering a reliable, secure, and user-friendly appointment system for Clinic Dr Hannani.